2021
DOI: 10.1155/2021/9234984
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Herbal Combinations and Pharmacological Mechanisms of Clinical Prescriptions for Coronary Heart Disease Using Data Mining and Network Pharmacology

Abstract: Though widely used in the treatment of coronary heart disease (CHD), the mechanism of traditional Chinese medicine (TCM) is still unclear because of its complex prescription rules. This study prospectively collected 715 prescriptions of TCM for the treatment of CHD. The characteristics of TCM in prescriptions were described and analyzed, and the rules of prescriptions were analyzed by using association rules. Frequency statistics showed that the high-frequency herbs with a frequency of more than 60% were Gan-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…It is generally believed that the more stable the ligand-receptor binding conformation, the lower the binding energy, and the binding energy < −4.25 kcal mol −1 can be considered to have the binding activity. Binding energy < −5.0 kcal mol −1 indicates a good binding activity, and binding energy < −7.0 kcal mol −1 indicates a strong binding activity [ 18 , 38 ]. It can be calculated from Figure 8 that the average binding energy of key ingredients and key targets was −7.5 kcal mol −1 , indicating that these ingredients and targets generally had strong binding activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that the more stable the ligand-receptor binding conformation, the lower the binding energy, and the binding energy < −4.25 kcal mol −1 can be considered to have the binding activity. Binding energy < −5.0 kcal mol −1 indicates a good binding activity, and binding energy < −7.0 kcal mol −1 indicates a strong binding activity [ 18 , 38 ]. It can be calculated from Figure 8 that the average binding energy of key ingredients and key targets was −7.5 kcal mol −1 , indicating that these ingredients and targets generally had strong binding activities.…”
Section: Resultsmentioning
confidence: 99%
“…The apriori algorithm was used in SPSS Modeler 18.0 software to conduct an association analysis on kidney meridian herbs [ 18 ]. According to “the support ≥ 15%, the confidence ≥ 85%, and the maximum number of antecedents was 2,” the core herbal combination of treating ROD with TCM was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…It has been the subject of various pharmacological studies, which have reported its therapeutic effects on numerous cardiovascular diseases. Bi et al (2021) used data mining to confirm that the frequency of yanhusuo in clinical prescriptions for the treatment of coronary artery disease in Chinese medicine is higher than 60%. In addition, previous studies have shown that yanhusuo extract and its constituents such as tetrahydropalmatie have the ability to reduce left ventricular end-diastolic pressure, enhance cardiac ejection function in rats, improve cardiac function, and significantly reduce the size of myocardial infarction, as well as having the ability to mitigate myocardial infarction with antiarrhythmic effects ( Ling et al, 2006 ; Wu et al, 2007 ; Tian et al, 2020 ; Han et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its primary active components are alkaloids ( Ling et al, 2006 ; Tian et al, 2020 ). Yanhusuo exhibits analgesic and sedative effects and significant therapeutic effects on coronary heart disease, angina pectoris, arrhythmia, and premature beats ( Bi et al, 2021 ). Importantly, it has low toxic side effects and is suitable for long-term use ( Tian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The network pharmacology was first proposed by Hopkins et al (Hopkins 2008) to overcome the so-called "one-drug/one-target/one-disease" approach in drug discovery. So far, several authors applied the network pharmacology approach mainly to elucidate the mechanism of action of several Chinese herbal medicine (Bi et al, 2021;Li et al, 2022;Wu et al, 2022). Wang et al through a network analysis identified a series of potential targets of TW in the treatment of DN.…”
Section: Introductionmentioning
confidence: 99%